RETINOIC ACID NUCLEAR RECEPTOR α (RARα) , A MAJOR ROLE IN MEDIATING RETINOIDS INHIBITION OF GROWTH IN HUMAN BREAST CARCINOMA CELLS - Shao, Zhimin; Shen, Zhenzho; Sheikh, M. Saeed; Fontana, Joseph A. (Chinese Journal of Cancer Research, 2013)
Retinoids mediate their actions via RARs (retinoic acid receptors ) and RXRs (retinoid X receptors ). Each classes of these nuclear retinoid receptor is further subdivided into three species namely α,βand γ Recent studies demnstrate that ER-positive HBC cell lines are sensitive and ER-negative cell lines are resistant to growth inhibitory effects of retinoic acid (RA). In this study we look at the expresion of RARs and RXRs in 6 HBC cell lines, we fotmd only RARα mRNA level was strong correlated with ER-status. To further investigate the major role of RARα in retinoid - mediated inhibition of growth, we transfected RARα cDNA in two RA- resistant ER- negative HBC cell lines. Analyses of different clonal populations of RARα transfectants from each cell line revealed growth inhibition by retinoids. Our results demonstrates that RARα plays a major role in mediating retinoids inhibition of gtowth in HBC cells and adequate levels are required for such actions.